1996
DOI: 10.1063/1.472256
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the trans-stilbene isomerization reaction in ethane

Abstract: A theoretical investigation of the experimental measurements of the isomerization rate of trans-stilbene in liquids is presented. Monte Carlo and molecular dynamics simulations of the reaction indicate that the predominant solvent effect is in raising the isomerization barrier in the potential of mean force as the solvent density is increased. Dynamic friction effects are small. Good agreement is obtained between the numerical and experimental rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…In Ref. 22 we used this potential to model the liquid phase thermal reaction of tS in ethane and found good agreement with Schroeder and Troe's experimental results measured 16 over a large range of ethane pressures. More recently, we used the same potential to model the isolated molecule energy dependent rates 23 and again found good agreement with experiment.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In Ref. 22 we used this potential to model the liquid phase thermal reaction of tS in ethane and found good agreement with Schroeder and Troe's experimental results measured 16 over a large range of ethane pressures. More recently, we used the same potential to model the isolated molecule energy dependent rates 23 and again found good agreement with experiment.…”
Section: Introductionsupporting
confidence: 56%
“…We modified it slightly 22 so that it gave an activation energy for the excited state reaction which agrees with the experimental measurement. In Ref.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Another approach, to construct a potential-energy surface suitable to reproduce selected spectroscopic data, has recently been conducted. [13][14][15][16] However, this procedure has little predictive power, since the desired results are put in previously, and then reproduced. Moreover, Eli Pollak and co-workers [17][18][19][20] apply sophisticated theories, based on transition state theory, to the photoisomerization of trans-stilbene.…”
Section: Introductionmentioning
confidence: 99%
“…The Stilbene isomerization reaction has attracted the attention of the research community for a long time and is a subject of extensive experimental and theoretical investigations. 16 In a recent series of papers, 9,17,18 using classical methods, we have shown that molecular dynamics on a ''good'' potential energy surface leads to excellent agreement between experiment and theory. We could thus resolve the long standing puzzle for the relation between experimentally measured gas phase and liquid phase rates which suggested that the liquid enhances the rate by a factor of ϳ20.…”
Section: Introductionmentioning
confidence: 99%